The theory of constraints and its implications for management accounting - Noreen, Eric W. (North River Press, 1995)
Presents the first in-depth evaluation of the theory of constraints (TOC) based on investigations at 21 US and European companies. In addition it provides a new development in the theory of constraints called the thinking process, which is no less than an attempt to bring systematic logic to bear on fundamental problems.